Analisis Minat Belajar Siswa terhadap PERubahan Hasil Belajar Ilmu Pengetahuan Sosial di SDN 104 Kota Utara Kota Gorontalo - Muhammad Sarlin (Universitas Cokroaminoto Palopo, 2018)
This study aims to determine the effect of student learning interest on Social Sciences. In research that becomes an indicator of research, namely perseverance in learning, awareness in learning; enthusiastic and like learning as an independent variable and learning outcomes as an indicator to see the extent of students' interest in learning social studies. The research method used in this research is quantitative by sampling using saturated sample methods because of the small population. As an instrument used to obtain valid data, namely the questionnaire so that the data in the study is primary data. Data analysis uses simple linear regression. The results of the analysis of this study indicate that there is a significant effect of Student Learning Interests on changes in student Learning Outcomes. The R Square number is 0.463. This value shows that as much as 46.3% of the variability in student learning outcomes can be explained by student learning interests, while the remaining 41.9% is influenced by other variables not examined in this study.